Fluoxetine, but not paroxetine, alters the jaw-closing muscle activity during non-rapid eye movement sleep in mice - Minako Ikeda; Ayako Mochizuki; Takafumi Kato; Shiro Nakamura; Kiyomi Nakayama; Masanori Dantsuji; Kazuyoshi Baba; Tomio Inoue (Neuroscience Research)
Sleep bruxism is an involuntary, exaggerated jaw-closing activity during sleep. Selective serotonin reuptake inhibitor (SSRI) use is a risk factor for bruxism. However, the effect of various SSRIs on masseter (jaw-closing) muscle activity remains unclear. Here, we examined the effects of long-term administration of two SSRIs, fluoxetine (FLX) and paroxetine (PRX), for 14 days on masseter muscle activity during wakefulness, non-rapid eye movement (NREM) sleep, and rapid eye movement (REM) sleep for 24 h in mice. Vigilance states were scored based on electroencephalographic, electrooculography and neck electromyographic (EMG) activities. The EMG activity of the masseter muscle was quantified in 6 h periods. FLX and PRX did not affect the duration of the three vigilance states. Both drugs significantly prolonged the REM sleep episode duration while decreasing the number of episodes. FLX significantly increased REM sleep onset latency. Neither FLX nor PRX affected the mean masseter EMG activity during wakefulness. FLX significantly increased the relative time of masseter muscle activity in NREM sleep during 02:00–08:00 and 08:00–14:00, while PRX did not affect three vigilance states. Overall, FLX had a limited but significant effect on masseter muscle activity in NREM sleep during specific periods.